Comparative Evaluation of Critical Path Method and Critical Chain Project Management for Ultra Low-Pressure Compressor Installation in the Oil and Gas Industry - Danur Widyanto; Lusi Ernawati; Samsu Dlukha Nurcholik; Rizqy Romadhona Ginting; Thorikul Huda (Department of Marine Engineering, Institut Teknologi Sepuluh Nopember, 2026)
Project delays remain a persistent challenge in the oil and gas industry, where conventional scheduling methods such as the Critical Path Method (CPM) fail to adequately address resource constraints and duration uncertainty. This study evaluates the effectiveness of Critical Chain Project Management (CCPM) as an alternative scheduling approach for Ultra-Low Pressure (ULP) compressor installation projects. A case study methodology was applied using actual project data from Pamaguan Plant, PT Pertamina Hulu Sanga Sanga, involving Work Breakdown Structure analysis, critical chain identification via Microsoft Project, and buffer sizing using the Root Square Error Method (RSEM). From 1,096 activities, 86 critical activities formed the critical chain, yielding a project buffer of 28 days and 27 feeding buffers. Buffer utilization reached 171%, placing the project in the red zone, indicating the planned buffer was insufficient to absorb delays caused by duration variability, resource limitations, and behavioral phenomena including Student Syndrome and Parkinson's Law. These findings confirm that CCPM offers a structurally superior scheduling framework compared to CPM, yet its effectiveness depends on disciplined execution and proactive buffer monitoring. This study contributes quantitative evidence on buffer utilization effectiveness in oil and gas project scheduling, providing practical guidance for managing high-complexity installation projects.